Cedar Cove : 1225 Christmas Tree Lane - Book 12 - Macomber, Debbie (Don Mills, Ont. : Mira, 2011)
As the holidays approach, Christmas tree farm owner Beth Morehouse finds her life taking some surprising turns when someone leaves a basket filled with puppies on her doorstep, and her daughters invite their dad, her long-divorced husband, Kent, to Cedar Cove in hopes of a mom-and-dad reunion.
Keywords: Divorced mothers -- Fiction; Mother-daughter relationship -- Fiction; Man-woman relationship -- Fiction; Cedar Cove (Wash. : Imaginary place) -- Fiction; Christmas -- Fiction; Romance